Half-plane edge and right angle wedge as elements causing diffraction in urban area - WALERIAN, Elżbieta (Archives of Acoustics, 1988)
This study analyzed the acoustic fields generated by interactions between acoustic waves and the edge of a half plane and a right angle wedge. Using known solutions of the diffraction of a monochromatic wave on a half-plane and a right angle wedge, they were written in a form permitting simultaneous analysis of three wave types: plane, cylindrical and spherical. Approximate forms of solutions were adopted and the ranges of their applicability analyzed. In the space around the chosen obstacle, its efficiency was calculated with respect to a free Geld, for wavelengths and distances of interest in urban acoustics.